Rajeshwar Prasad’s ‘Righteousness’ as a Timeless Epic for the Human Soul - Kumar Singh, Balendra (International Journal of Language and Literary Studies, 2026)
The research article establishes that Righteousness is an essential element in comparative literary studies because it demonstrates how an Indo-Anglian allegorical epic presents two distinct aspects: individual pain and universal justice. The research shows that Rajeshwar Prasad uses a Christ-like protagonist to create a new definition of heroism, demonstrating how people can develop moral strength through their battle against oppressive forces rather than achieving success through predetermined paths. The novel uses spiritual symbols to create a structured narrative of loss, demonstrating an epic purpose that offers readers hope through a culturally specific yet worldwide-applicable template. The study demonstrates how modern allegorical fiction uses personal loss and communal moral restoration to create new pathways for research about its global reach.